2011
DOI: 10.1111/j.1468-3083.2011.03983.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid levels in patients with lichen planus: a case–control study

Abstract: The results obtained in this study indicate an association between LP and dyslipidaemia. Lipid levels screening in men or women with LP may be useful to detect individuals at risk and start preventive treatment against the development of cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 14 publications
7
32
2
2
Order By: Relevance
“…Cytokines such as TNF-a, IL-2 and IL-6 have been responsible for elevated lipid levels in patients with psoriasis. IL-6 is the main proinflammatory cytokine that stimulates the hypothalamic pituitary axis responsible for central obesity, hypertension and insulin resistance [8,13,17]. Activation of inflammatory cells and released cytokines and proteases lead to psoriatic lesions and atherosclerotic plaque formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokines such as TNF-a, IL-2 and IL-6 have been responsible for elevated lipid levels in patients with psoriasis. IL-6 is the main proinflammatory cytokine that stimulates the hypothalamic pituitary axis responsible for central obesity, hypertension and insulin resistance [8,13,17]. Activation of inflammatory cells and released cytokines and proteases lead to psoriatic lesions and atherosclerotic plaque formation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that a chronic inflammatory state may cause increased risk for cardiovascular diseases such as atherosclerosis, myocardial infarction (MI) and stroke in patients with psoriasis [5,6]. It has also been shown that LP is associated with dyslipidemia, and the inflammatory process may lead to lipid metabolism disorders such as an increase in serum triglyceride (TG) levels and a decrease in high-density lipoprotein (HDL) levels [7,8]. As with psoriasis, LP is also a chronic inflammatory disease, and chronic inflammation is regarded as a part of the MS [9].…”
Section: Introductionmentioning
confidence: 99%
“…Lichen planus (LP) is a chronic inflammatory disease that affects the skin and mucous membranes [1]. Although its aetiology and pathogenesis are not fully understood, LP is believed to be a T-cell-mediated inflammatory disease.…”
Section: Introductionmentioning
confidence: 99%
“…Literatürde hem oral hem kutanöz LP' de oksidatif stresi araştıran tek makale yer almaktadır 9 . LP etiyolojisi açısından incelendiğinde, ayrıca çeşitli yayınlarda dislipidemi, tiroid hastalıkları, hepatit C enfeksiyonu ve otoimmün hastalıklarla da ilişkilendirilmiştir 2,3,[14][15][16][17][18][19][20][21][22][23] . Kronik enflamasyon ve metabolik sendrom ilişkisi nedeniyle, LP patogenezinde dahil olan enflamatuvar olaylar, LP'nin çeşitli sistemik hastalıklarla da birlikteliğini açıklayabilir 3,15,24 .…”
Section: Introductionunclassified